Features of clinical complexity in european patients with atrial fibrillation: a report from the ESC-EHRA EORP atrial fibrillation general long-term registry. (3rd October 2022) - Proietti, M; Romiti, G F; Vitolo, M; Bonini, N; Fawzy, A M; Ding, W Y; Fauchier, L; Marin, F; Nabauer, M; Potpara, T S; Dan, G A; Boriani, G; et al.
Abstract: Introduction: There is increasing concern regarding the burden of clinical complexity, beyond thromboembolic risk, in patients with atrial fibrillation (AF). Also, clinical complexity is heterogenous and entails differential impact on the patients' clinical course. Purpose: To explore different complexity features in AF patients in determining differences in clinical management and outcomes. Methods: We analyzed patients enrolled in the ESC-EHRA EORP-AF General Long-Term Registry. Features of complexity were analysed in the context of the following high-risk groups: i) only CHA2DS2-VASc ≥2; ii) history of stroke/bleeding; iii) chronic kidney disease (creatinine clearance <60 mL/min, CKD); iv) frail (frailty index ≥0.25); v) ≥2 criteria. All these groups were compared to a low-risk group (CHA2DS2-VASc 0–1). We examined use of oral anticoagulant (OAC) and the risks of a composite outcome of all-cause death and major adverse cardiovascular events. Results: A total of 10285 patients (mean [SD] age 68.8 [11.5] years, 4107 [39.9%] females) were included in the analysis. Of these, 3944 (38.3%) had only CHA2DS2-VASc ≥2; 412 (4.0%); history of stroke/bleeding; 1480 (14.4%) CKD; 1007 (9.8%) were frail; 1315 (12.8%) had ≥2 criteria; and 2127 (20.7%) were low-risk. After adjustment for age, sex, type of AF and EHRA score, compared to low-risk patients, all the other groups were associated with OAC prescription but with progressively lower odds ratio, while those ≥2 criteria which were least likely prescribed with OAC (Table 1). After a mean (SD) 634.5 (223.0) days of follow-up, a total of 1432 events were recorded. After adjustment for confounders, Cox regression analysis found that all the complexity groups were associated with a higher risk of the composite outcome across the groups (Figure 1). In patients with available data about ABC (Atrial fibrillation Better Care) pathway adherence, the latter adherence was associated a significant incidence rate reduction (IRR) compared to non-ABC adherence in those with ≥2 criteria of clinical complexity (IRR 0.46, 95% CI 0.30–0.71), and in the CKD complexity group (IRR 0.57, 95% CI 0.41–0.81). Conclusions: In a large contemporary cohort of European AF patients, features of clinical complexity affect differently prescriptions of OAC. All the subgroups of clinical complexity were associated with a higher risk of adverse outcomes, which were reduced by adherence to ABC pathway. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Since the start of EORP, the following companies have supported the programme: Abbott Vascular Int. (2011–2021), Amgen Cardiovascular (2009–2018), AstraZeneca (2014–2021), Bayer (2009–2018), Boehringer Ingelheim (2009–2019), Boston Scientific (2009–2012), The Bristol Myers Squibb and PfizerAlliance (2011–2016), The Alliance Daiichi Sankyo Europe GmbH and Eli Lilly and Company (2011–2017), Edwards (2016–2019), Gedeon Richter Plc. (2014–2017), Menarini Int. Op. (2009–2012), MSD-Merck & Co. (2011–2014), Novartis Pharma AG (2014–2020), ResMed (2014–2016), Sanofi (2009–2011), SERVIER (2010–2021), and Vifor (2019–2022).